Analysis of land use (2013-2022) in the Gayo highlands, Aceh, Indonesia - Arico, Zulfan; Rahmawaty; Delvian; Hamdani Harahap; Mohd Hasmadi Ismail (Talenta Publisher, 2023)
Forest fragmentation is a threat to ecosystems in Indonesia caused by forest conversion to plantations. This study aims to analyze the use of land cover in the period 2013-2022. The research was conducted from November 2022 to January 2023 in the Gayo highland area by taking case studies in 2 regions including the Central Aceh District and Bener Meriah District. The research was carried out in several stages, namely: image pre-processing, image visual interpretation, making image classification class identifiers, and ground checking. The pre-processing stage is the preparation of tools and materials. Landsat 8 OLI imagery for the study area downloaded from the United States Geological Survey (USGS) website. The results of the research show that in the last 10 years there has been a decrease in the area of land cover in the exploration area of primary forest and secondary forest. Meanwhile, in the cultivation of dry fields, settlements, plantations and vacant land, land use has increased. Changes in the use of land cover are influenced by community activities in Central Aceh and Bener Meriah Regencies.